PENGELOLAAN RETRIBUSI PARKIR DI KECAMATAN BANGKINANG KOTA TAHUN 2022 - Yasri, Kevin Assidiqi; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the lack of supervision of parking attendants, resulting in parking fees not being in accordance with local regulations, the public's lack of awareness regarding the importance of parking fees, and the lack of supporting infrastructure.The purpose of this research is to understand and describe the Management of Parking Retribution by the Kampar Regency Transportation Agency in Bangkinang City District in 2022.The theory used according to George G Terry is Planning, Organizing, Implementation, and Supervision.The method used in this research is qualitative with a descriptive approach.The sources of this research are the Head of the Parking UPT, parking coordinators, parking attendants, vendors, and the community as users of parking services.The data collection technique used interviews and document reviews such as journals and news media.The data analysis technique is conducted qualitatively based on the results of interviews and document reviews such as articles and news media.The research results indicate the management of parking fees.Parking fee management can run well by applying management functions such as planning, organizing, implementing, and supervising.The management planning carried out involves setting targets, but these have decreased compared to the previous year, and the determination of parking locations has also decreased due to suboptimal conditions and a lack of public awareness regarding the importance of parking fees.OrganizingOrganizing involves the division of labor according to job functions and the process of departmentalization.The use of facilities and infrastructure is still inadequate, and there are individuals who are undisciplined in their duties.The implementation carried out includes the issuance of a work agreement letter to the second party, and parking attendants who do not provide tickets and charge fees that do not comply with local regulations.Direct supervision is carried out to check what is happening on the ground, while indirect supervision is seen from income reports and reports from parking users. Keyword:management, parking, tickets, parking fees.